Cardiovascular risk stratification in rheumatic diseases: carotid ultrasound is more sensitive than Coronary Artery Calcification Score to detect subclinical atherosclerosis in patients with rheumatoid arthritis. Issue 11 (13th July 2013) - Corrales, Alfonso; Parra, José A; González-Juanatey, Carlos; Rueda-Gotor, Javier; Blanco, Ricardo; Llorca, Javier; González-Gay, Miguel A
Abstract : Objective: To determine the ability of Coronary Artery Calcification Score (CACS) and carotid ultrasonography in detecting subclinical atherosclerosis in rheumatoid arthritis (RA). Methods: A set of 104 consecutive RA patients without history of cardiovascular (CV) events were studied to determine CACS, carotid intima-media thickness (cIMT) and plaques. Systematic Coronary Risk Evaluation (SCORE) modified according to the EULAR recommendations (mSCORE) was also assessed. Results: The mean disease duration was 10.8 years, 72.1% had rheumatoid factor and/or anti-CCP positivity and 16.4% extra-articular manifestations. Nine were excluded because they had type 2 diabetes mellitus or chronic kidney disease. CV risk was categorised in the remaining 95 RA patients according to the mSCORE as follows: low (n=21), moderate (n=60) and high/very high risk (n=14). Most patients with low mSCORE (16/21; 76.2%) had normal CACS (zero), and none of them CACS>100. However, a high number of patients with carotid plaques was disclosed in the groups with CACS 0 (23/40; 57.5%) or CACS 1–100 (29/38; 76.3%). 72 (75.8%) of the 95 patients fulfilled definitions for high/very high CV as they had an mSCORE ≥5% or mSCORE <5% plus one of the following findings: severe carotid ultrasonography findings (cIMT>0.9 mm and/or plaques) or CACS>100. A CACS>100 showed sensitivity similar to mSCORE (23.6% vs 19.4%). In contrast, the presence of severe carotid ultrasonography findings allowed identifying most patients who met definitions for high/very high CV risk (70/72; sensitivity 97.2% (95% CI 90.3 to 99.7)). Conclusions: Carotid ultrasonography is more sensitive than CACS for the detection of subclinical atherosclerosis in RA.